ACT001 synergizes with temozolomide-based chemoradiotherapy to cure refractory glioblastoma by targeting TNF-CXCL10-CD8+ T-cell immunity - Shu, Ya; Ding, Ze-hua; Gao, Pan-pan; An, Qi; Wu, Li-qin; Zhang, Xin-ran; Jiang, Hai-feng; Miao, Cheng; Peng, Mei-ting; Chen, Xiao-qian; Cai, Jun; Liu, Feng (Frontiers in Pharmacology, 2026)
Glioblastoma multiforme (GBM), a highly invasive brain tumor, is severely restricted in T-cell infiltration and anti-tumor activity due to its immunosuppressive microenvironment. However, commonly used preclinical GBM mouse models cannot fully recapitulate the refractoriness of human GBM or effectively distinguish therapeutic efficacy. In this study, we evaluated the efficacy and mechanisms of therapies based on the novel sesquiterpene lactone small-molecule compound, ACT001, using the refractory G422TN-GBM mouse model. ACT001 alone exerted evident anti-G422TN-GBM effects in vivo and in vitro, but it only slightly prolonged animal survival. ACT001 combined with concurrent radiotherapy and temozolomide (RT/TMZ) exerted synergistic effects by suppressing tumor progression and extending animal survival. Importantly, the RT/TMZ/ACT001 regimen could achieve cure (long-term survival, >100 d, 26.7%) and immune cure (passing the tumor-rechallenge assay, >100 d, 12.5%) in G422TN mice. However, combining the anti-PD-1 antibody (αPD-1) with RT/TMZ/ACT001 did not further improve survival. Mechanistically, RT/TMZ/ACT001 substantially activated the tumor necrosis factor (TNF) pathway, inducing tumor cells and stromal cells in the microenvironment to express the chemokine C-X-C motif chemokine 10 (CXCL10), thereby promoting T-cell infiltration, especially CD8+ T cell, into the tumor site. Pharmacological inhibition of the TNF signaling pathway with R-7050 completely abolished the synergistic efficacy of RT/TMZ/ACT001. Taken together, our results demonstrate that ACT001 combined with RT/TMZ can overcome the immunosuppressive barrier of GBM to achieve immune cure in GBM via TNF-CXCL10-CD8+ signaling, strongly suggesting the priority of combining ACT001 with RT/TMZ rather than with αPD-1 in clinical trials.